2021
DOI: 10.1007/s11010-021-04107-3
|View full text |Cite
|
Sign up to set email alerts
|

Status of mannose-binding lectin (MBL) and complement system in COVID-19 patients and therapeutic applications of antiviral plant MBLs

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by a virus called "Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)." In the majority of patients, infection with COVID-19 may be asymptomatic or may cause only mild symptoms. However, in some patients, there can also be immunological problems, such as macrophage activation syndrome (CSS) that results in cytokine storm syndrome (CSS) and acute respiratory distress syndrome (ARDS). Comprehension of host-microbe communications is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 178 publications
(338 reference statements)
0
46
0
Order By: Relevance
“…Owing to their smaller size, compared to other plant Man-specific lectins, Man-specific lectins from cyanobacteria such as CVN-N (cyanovirin), MVN (microvirin), and AH (actinohivin) from actinobacteria, have been deeply investigated for their anti-viral properties. In addition, only very few publications report the ability of Man-specific lectins from higher plants to interact with glycans of the coronavirus envelope [ 13 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their smaller size, compared to other plant Man-specific lectins, Man-specific lectins from cyanobacteria such as CVN-N (cyanovirin), MVN (microvirin), and AH (actinohivin) from actinobacteria, have been deeply investigated for their anti-viral properties. In addition, only very few publications report the ability of Man-specific lectins from higher plants to interact with glycans of the coronavirus envelope [ 13 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings may have important implications such as the prioritization of individuals with B variants during vaccination strategies ( Gupta and Gupta, 2021 ) , or the encouragement of the affected individuals to receive mannose-specific plant lectins in an attempt to prevent a poor outcome after SARS-CoV-2 infection, as also suggested for other coronaviruses infections ( Medetalibeyoglu et al, 2021 ) .…”
Section: Discussionmentioning
confidence: 74%
“…In our study, we demonstrated that the presence of the B allele (rs1800450) of the MBL2 gene was significantly associated with a worse clinical phenotype in COVID-19 patients, and particularly with pneumonia development. The contribution of MBL deficiency in human infectious and non-infectious diseases has been established in several studies (reviewed by Gupta & Gupta, 2020) ( Gupta and Gupta, 2021 ). Thus, Liu et al reported that low levels of MBL are associated with an increased risk of community-acquired pneumonia and a greater risk of death ( Liu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannose‐binding lectin (MBL; also referred to as mannan‐binding lectin and mannose‐binding protein), is a pattern recognition innate immune molecule and involved in the protection of the host against viral infections. 89 , 90 IBV is a contagious avian coronavirus that can infect respiratory tract of chicken and in poultry industry is a major problem. 91 Zhang et al.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%